Access From Above—Bailout Solution for Intraoperative Distal Migration of Abdominal Aortic Stent Graft. (July 2017) - Kuhelj, Dimitrij; Avsenik, Jernej; Nuredini, Dašmir
The majority of the ruptured abdominal aortic aneurysms today is treated endovascularly. In cases with short aneurysm neck, chimney technique can be used to extend landing zone in emergency setting. Additionally, the repositioning ability of C3 delivery system (Gore & Associates) allows better positioning in cases with challenging anatomy. In our experience, proximal reposition of partially deployed device can be problematic in some patients. We present a case of endovascular repair of ruptured abdominal aortic aneurysm using chimney technique where proximal reposition was achieved by snaring the aortic device via axillary access.